Structural, electronic structure and magnetic studies of GdFe1-xNixO3 (x <= 0.5) - Bashir, Abida; Ikram, M.; Kumar, Ravi; Lisboa Filho, Paulo Noronha [UNESP] (Elsevier B.V. Sa, 2012)
The structural, electronic structure and magnetic properties of Ni doped GdFeO3 perovskite materials have been studied. A decreasing trend in volume with the increasing Ni concentration without any structural change is confirmed from X-ray diffraction studies. The electronic structural studies show that the competing ions within the ensemble have +3 oxidation states, which includes the Gd, Fe and Ni ions, and also confirms the octahedral symmetry of the Fe/Ni ions. The magnetic properties clearly depict that the Ni doping can tailor the phase transitions arising due to temperature/field dependence having a heavy impact on spin dynamics. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: XRD; X-ray absorption spectroscopy; Magnetization